Strong Aggregation‐Induced CPL Response Promoted by Chiral Emissive Nematic Liquid Crystals (N‐LCs) - Li, Xiaojing; Li, Qian; Wang, Yuxiang; Quan, Yiwu; Chen, Dongzhong; Cheng, Yixiang (Chemistry : a European journal, 2018)
In this paper we designed a kind of aggregation‐induced emission (AIE) chiral fluorescence emitters (R/S‐BINOL‐CN enantiomers) in the aggregate state. Chiral emissive nematic liquid crystals (N*‐LCs) prepared by doping this kind of AIE‐active R/S‐BINOL‐CN enantiomers into a common achiral nematic liquid crystal (N‐LC, E7) can self‐assemble as the regularly planar Grandjean texture leading to high luminescence dissymmetry factor (glum) of aggregation‐induced circularly polarized luminescence (AI‐CPL) signal up to 0.41, which can be attributed to dipolar interactions from polar cyano groups and π–π interactions between binaphthyl moiety of the dopant R/S‐BINOL‐CN and biphenyl group of the host molecules (E7). Chiral emissive nematic liquid crystals (N*‐LCs) prepared by doping AIE‐active R/S‐BINOL‐CN enantiomers into N‐LCs (E7) can self‐assemble as the regularly planar Grandjean texture leading to high luminescence dissymmetry factor (glum) of aggregation‐induced CPL signal up to 0.41.